Herbal supplements in Jordan: a cross-sectional survey of pharmacists’ perspectives and knowledge - Abdallah Y Naser; Michael Heinrich; Banaz Jalil; Jose M Prieto (BMJ Open)
Objectives Pharmacists are ideal partners for engaging with the needs and expectations of patients. They can play a vital role by providing information and supplying herbal medicines. In some community settings, pharmacists are also the main first point of care. This study explored Jordanian community pharmacists’ perspectives and knowledge of herbal medicines available in pharmacies.Design A cross-sectional study using an online survey was developed, and it was distributed via social media platforms. The one-way analysis of variance (ANOVA) test was used to compare the mean knowledge scores between different demographic groups. Multiple linear regression analysis was used to identify predictors of herbal medicines knowledge.Setting Jordanian community pharmacies.Participants 401 Jordanian community pharmacists.Results Herbal supplements are sold in practically all pharmacies (98.5%). Slimming aids (14.7%), followed by sexual and sports enhancements (14%) and maintaining general health (12.1%) were most requested by Jordanian customers. While supplements for maintaining general health (12%), followed by slimming aids (11.4%) and skin conditions (9.3%) were most recommended by Jordanian pharmacists. 63.1% were not aware of potential herb–drug interactions, 95.6% did not receive complaints from customers about herbal medicines and 41.2% would not report adverse reactions to the national pharmacovigilance services. The mean knowledge score for knowledge of use, regulation, adverse reactions, and drug interactions was 3.7 (SD: 0.7), 3.5 (SD: 0.8), 3.6 (SD: 0.8), and 3.6 (SD: 0.8) (out of 5), respectively. ANOVA test showed that total pharmacists’ knowledge scores significantly differed based on the length of time practising pharmacy (p<0.05).Conclusion This study highlights some key concerns relating to recommendations, awareness and reporting of herbal medicines among Jordanian community pharmacists. Pharmacists need enhanced education to provide objective and evidence-based information on the benefits–risks of herbal medicines. Future studies need to be carried out to confirm whether our findings are transferable to other Middle Eastern countries.